The notes on the special tube surfaces generated by normal curves in E24 - Almaz, Fatma; Alyamac Kulahci, Mihriban (Soc Paranaense Matematica, 2025)
In this work, the special tube surfaces generated by normal curves with Frenet frame in E24 are examined and some certain results of describing the surface characterizations on the surfaces are presented in detail. Moreover, using the Gaussian curvatures and mean curvatures of tube surfaces with normal curve generated by Frenet frame in E24, the conditions being Weingarten surface and HK-quadric surface, minimal surface, flat, ... etc are examined in detail.
Keywords: Semi-Euclidean Space E24; tube surfaces; weingarten surface; normal curve